Deciphering the structural style of the deformation front in the western Central Andes: insight from the Sierra de Moreno in northern Chile - F. Martínez; C. López; G. Fuentes; L. Ayala-Carazas; R. Butler; C. Arriagada; L. Mandiola; C. Torres (Tectonophysics, 2026)

Chilling Consequences: Recruitment Failure of Four Native Fish Species in a Thermally Polluted, Regulated River - Laura E. Michie; James N. Hitchcock; Simon M. Mitrovic; Matthew Gordos; Gavin L. Butler (Fisheries Management and Ecology, 2026)
Cold water pollution (CWP), caused by the release of unseasonably cool water from the bottom of large reservoirs to downstream rivers, is an escalating global threat to riverine biodiversity that is exacerbated by future dam developments and climate change. This study examined the impact of CWP on native fish populations in the Severn River (NSW, Australia), downstream of a large reservoir. Long‐term data (2012–2024) revealed chronic CWP, with thermal regimes frequently below thresholds required for native fish spawning during the austral summer period. An aged population structure and chronic recruitment failure were evident in four native fish species. Additionally, native fish stocking efforts have resulted in limited success. We recommend both long‐term CWP mitigation and immediate adaptive management strategies, such as optimising stocking practices and opportunistic water management actions, as critical to sustaining native fish populations.

Lace monitors scavenge the large carcass of an endangered eastern freshwater cod - Brendan C. Ebner; John St Vincent Welch; Leo M. Cameron; Jason Schaffer; Gavin L. Butler (Food Webs, 2026)

Practical application of BREAM2 in bystander/resident spray drift exposure assessments: accounting for variations in water volume - Kathrin Bürling; Edgars Felkers; Christian J. Kuster; Siân L. Wright-Williams; M. Clare Butler Ellis (Journal of Consumer Protection and Food Safety, 2026)
The EFSA 2022 guidance on non-dietary human exposure, including operators, workers, residents and bystanders, relies on output from the original BREAM model, including simplified extrapolation for different application volumes. This study aims to present the current limitations and challenges in the European Plant Protection Product (PPP) authorizations for non-dietary exposure and risk assessments of residents and bystanders. It also and outlines a concept that could help overcome these limitations while maintaining a health-protective approach. The study demonstrates that refining the value of spray liquid (mL/ person) by more reliably incorporating application volume as a variable in the model leads to a more realistic and scientifically sound risk assessment. This refined approach has been shown to be both reasonable and applicable in the context of PPP registration processes, ahead of its anticipated inclusion in the next EFSA guidance update, where the implementation of BREAM2 is expected.

Cryptic foreland basin strata of the southeastern Trans-Hudson Orogen revealed by detrital zircon geochronology - Jared P. Butler; Alana M. Hinchey; James L. Crowley (Precambrian Research, 2025)

How population control of pests is modulated by density dependence: The perspective of genetic biocontrol - Cole D. Butler; Alun L. Lloyd (Journal of Theoretical Biology, 2025)

Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

Genetic control of stem elongation in common bean and the influence of age and flowering time - Chantelle J. Beagley; Jacqueline K. Vander Schoor; Jakob B. Butler; James L. Weller (Theoretical and Applied Genetics, 2025)
Key message Genetic analysis of stem elongation in common bean identified loci acting at different developmental stages and reveals interactions with flowering time. Abstract Stem internode elongation is a major determinant of growth habit and plant height, and is often responsive to environmental signals, making it an integral component of plant architecture and a core characteristic targeted for crop improvement. More effective exploitation of stem elongation requires increased understanding of not only major determinants, but also of more subtle, specific influences as breeders seek to further refine adaptation to local growing environments. Common bean is a globally important legume crop and exhibits extensive variation in stem elongation, but there is little knowledge about the underlying genetic control. To better understand this trait, we performed a comprehensive genetic analysis in a wide F 2 cross between wild and domesticated bean. By conducting quantitative trait locus (QTL) analyses of the length of individual internodes, we discovered four main genomic regions influencing internode length at different stages of development. Of these, one demonstrated strong association with the two known flowering genes Fin and Ppd on chromosome 1, while two other regions were validated in subsequent F 3 and F 4 generations and were demonstrated to be independent of flowering time. These results highlight the complex dynamic nature and potential pleiotropic interactions of elongation genes throughout development, and indicate new avenues of inquiry towards improving crop adaptation to specific environments.

Comparison of the air kerma standards of ARPANSA, Australia, and the IAEA in RQR, RQA, and RQT diagnostic X-ray beams - Kam L. Lee; Zakithi Msimang; Duncan Butler; Peter Thomas; Joao Cardoso (Physical and Engineering Sciences in Medicine, 2025)
A comparison of air kerma standards between the Australian Radiation Protection and Nuclear Safety Agency (ARPANSA) and the International Atomic Energy Agency (IAEA) was carried out for the RQR, RQA and RQT radiation qualities (as prescribed by IEC 61267 or IAEA TRS 457) using two ionisation chambers as transfer standards. The ratios between the IAEA and ARPANSA calibration coefficients ranged between 0.993 and 0.997 for RQR beams, 0.990 and 0.999 for RQA beams, and 0.993 to 0.994 for RQT beams. The relative expanded uncertainty for IAEA and ARPANSA was 1.2 and 1.4% respectively, and the comparison results agree at around the level of, or better than, the combined standard uncertainty of 0.74% for all the beams.

Performance of summary measures of core body temperature in heat-related health outcome regression models - M. Dally; A. Dye-Robinson; Y. Li; D. Jaramillo; K. Villarreal-Hernandez; L. Krisher; J. Butler-Dawson; J. Schaeffer; J. L. Adgate; K. A. James; L. S. Newman (International Journal of Biometeorology, 2025)

Phenology and yield do not scale from single row to whole plot in chickpea and lentil - L. Lake; R. Gimenez; R. Ortega Martinez; J. L. Weller; M. Javid; J. B. Butler; L. E. James; M. F. Dreccer; R. French; C. M. Cossani; J. E. Hayes; V. O. Sadras (Euphytica, 2025)
Reliable phenotyping is critical for pre-breeding and breeding. Some traits such as herbicide tolerance are more likely to scale from plant to crop than others such as yield. Here we compared phenology, yield and its components in two arrangements—single rows and whole plots—for 10 chickpea and 10 lentil cultivars in 11 (chickpea) and 10 (lentil) Australian environments resulting from the combination of location, season, and sowing date. The cultivars were characterised for key genetic loci for phenology: Elf3a , GI and the FT gene cluster in chickpea, and GWAS-chr2 and the FTb gene cluster in lentil. Across environments, yield of chickpea ranged from 33 to 268 g per lineal m (g m −1 ) in single rows and 5 to 77 g m −1 in whole plots, and yield of lentil ranged from 20 to 174 g m −1 in single rows and 9 to 104 g m −1 in whole plots. Across environments and genotypes, time to flowering was later in 207 of 275 chickpea whole plots compared with single rows and in 175 out of 234 lentil whole plots compared with single rows. In both chickpea and lentil, flowering and podding varied with the interaction between genotype, arrangement, and environment, resulting in altered genotypic rankings between single row and whole plot within and between environments. Yield components were variably affected by the three-way interaction; biomass was the only trait showing no interaction in either crop. Broad sense heritability of seed size fell from 0.60 in whole plots to 0.37 in single rows for chickpea, and from 0.87 to 0.62 in lentil. We highlight the need to understand scaling for agronomically important traits to avoid wasteful or counterproductive phenotyping and breeding efforts.

Freshwater fish condition responses to hydrological disturbance are species‐ and scale dependent - Maxwell C. Mallett; Jason D. Thiem; Gavin L. Butler; Luke Carpenter‐Bundhoo; Mark J. Kennard (Journal of Fish Biology, 2025)
Modification of river flows is a major cause of freshwater fish population declines in many parts of the world. Identifying the precise mechanisms of these declines represents a significant challenge, as a range of stressors can simultaneously impact various components of fish health, fitness and population dynamics. Here we investigate the role of river flows and other biophysical factors on spatio‐temporal variation in freshwater fish body condition in Australia's highly modified Murray‐Darling Basin using three widely distributed native (Murray cod Maccullochella peelii , golden perch Macquaria ambigua and bony herring Nematalosa erebi ) and one introduced (common carp Cyprinus carpio ) species. Our aim was to uncover drivers of spatio‐temporal variation in fish condition at two spatial extents: at the basin scale, utilising a flow regime disturbance index, and at the river‐valley scale, employing individual flow gauge data to assess responses in fish condition to multiple measures of antecedent (365 day) flow. Linear mixed effects modelling revealed that at the basin scale, M. peelii and M. ambigua were in better condition in rivers with lower flow regime disturbance, and temporal trends in the condition of N. erebi , C. carpio and M. peelii reflected boom and bust dynamics related to wet and dry climate periods. At the river‐valley scale, mean antecedent daily flow magnitude was significantly positively related to the condition of M. peelii , M. ambigua and C. carpio , whereas the number of high‐flow days was negatively related to condition of N. erebi . Our study demonstrates that a simple body condition index calculated from routinely collected length–weight data is sensitive to multiple measures of hydrological disturbance in river systems that experience substantial temporal and spatial variability. We emphasise that studies considering multiple spatial scales are important for understanding complex scale‐dependent mechanisms influencing fish condition.

Survival Estimates of Endangered Shortnose Sturgeon (Acipenser brevirostrum Lesueur, 1818) from Geographically Disjunct Population Segments - Evan C. Ingram; Amanda L. Higgs; Liam Butler; Dewayne A. Fox; Adam G. Fox (Fishes, 2025)
The complex life history and stock structure of endangered shortnose sturgeon (Acipenser brevirostrum) may hinder recovery efforts for individually managed river populations in the US. Reliable survival estimates are essential for evaluating population trends and guiding conservation amid ongoing and emergent threats. However, such estimates are scarce in the recent literature and available for only a few wild populations, with their usefulness in practical management limited. In this study, we leverage multi-year acoustic telemetry data from monitoring projects in the Hudson River, New York (2012–2015), and Altamaha River, Georgia (2011–2014), to develop and compare survival estimates for spawning populations at opposite ends of the species’ US geographic range. Bayesian multistate capture–recapture models indicated high and precise apparent monthly adult survival in both the Hudson (0.991; 95% Bayesian credibility interval [CI]: 0.984–0.996) and Altamaha (0.980; 95% CI: 0.969–0.989) rivers, with implied annual survival rates of 0.897 and 0.787, respectively. Overall, this study advances our understanding of clinal variation in key demographic parameters and underscores the need to develop regionally specific goals for recovery. Broadening the estimates through increased telemetry coverage and integration of additional data will strengthen recovery efforts and support the long-term persistence of shortnose sturgeon across their range.

Exotic plant responses to large-scale commercial logging in ponderosa pine forests of the Black Hills National Forest, South Dakota, USA - Jack L. Butler; Stefanie D. Wacker; Jacqueline P. Ott; Scott Baggett; Michael A. Battaglia (Forest Ecology and Management, 2025)

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Effects of maternal contact and positive human contact during lactation on pork quality: Positive human contact to piglets during lactation improves pork loin muscle pH - Katelyn Tomas; Jemma Savaglia; Robert J.E. Hewitt; Kate J. Plush; Darryl N. D'Souza; Kym L. Butler; Paul H. Hemsworth; Alan J. Tilbrook (Meat Science, 2025)

Generalized Stomatal Optimization of Evolutionary Fitness Proxies for Predicting Plant Gas Exchange Under Drought, Heatwaves, and Elevated CO 2 - Aaron Potkay; Antoine Cabon; Richard L. Peters; Patrick Fonti; Gerard Sapes; Anna Sala; Artur Stefanski; Ethan Butler; Raimundo Bermudez; Rebecca Montgomery; Peter B. Reich; Xue Feng (Global Change Biology, 2025)
Stomata control plant water loss and photosynthetic carbon gain. Developing more generalized and accurate stomatal models is essential for earth system models and predicting responses under novel environmental conditions associated with global change. Plant optimality theories offer one promising approach, but most such theories assume that stomatal conductance maximizes photosynthetic net carbon assimilation subject to some cost or constraint of water. We move beyond this approach by developing a new, generalized optimality theory of stomatal conductance, optimizing any non‐foliar proxy that requires water and carbon reserves, like growth, survival, and reproduction. We overcome two prior limitations. First, we reconcile the computational efficiency of instantaneous optimization with a more biologically meaningful dynamic feedback optimization over plant lifespans. Second, we incorporate non‐steady‐state physics in the optimization to account for the temporal changes in the water, carbon, and energy storage within a plant and its environment that occur over the timescales that stomata act, contrary to previous theories. Our optimal stomatal conductance compares well to observations from seedlings, saplings, and mature trees from field and greenhouse experiments. Our model predicts predispositions to mortality during the 2018 European drought and captures realistic responses to environmental cues, including the partial alleviation of heat stress by evaporative cooling and the negative effect of accumulating foliar soluble carbohydrates, promoting closure under elevated CO 2 . We advance stomatal optimality theory by incorporating generalized evolutionary fitness proxies and enhance its utility without compromising its realism, offering promise for future models to more realistically and accurately predict global carbon and water fluxes.

Measuring the association between the opening of a new multi-national restaurant with young people's eating behaviours - Helen J. Moore; Claire L. O'Malley; Scott Lloyd; Fatemeh Eskandari; Kelly Rose; Mark Butler; Tim G. Townshend; Heather Brown; Daniel Clarkson; Amelia A. Lake (Appetite, 2024)

Variation in lifetime movements of an Ariidae species in an eastern Australian river revealed by otolith microchemistry - Lauren J. Stoot; Gregory S. Doran; Jason D. Thiem; Gavin L. Butler; An V. Vu; Lee J. Baumgartner (Estuarine, Coastal and Shelf Science, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Change point detection of events in molecular simulations using dupin - Brandon L. Butler; Domagoj Fijan; Sharon C. Glotzer (Computer Physics Communications, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Data driven food fraud vulnerability assessment using Bayesian Network: Spices supply chain - Y. Bouzembrak; N. Liu; W. Mu; A. Gavai; L. Manning; F. Butler; H.J.P. Marvin (Food Control, 2024)

Spatial variability in water strontium isotopes and trace metals from the Clarence River Basin, New South Wales, Australia - Lauren J. Stoot; Lee J. Baumgartner; Gavin L. Butler; Jason D. Thiem; Brett M. Knowles; Gregory S. Doran (Hydrobiologia, 2024)
Understanding fish movement in river systems is essential in identifying habitats which are important for species to perpetuate. Water chemistry, paired with fish otoliths, can be used to trace movements among different habitats, although a detailed understanding of spatial variation in water chemistry is first required. To obtain this knowledge, we analysed surface water collected from 59 sites throughout the Clarence River Basin, a coastal river basin in northern New South Wales, Australia. The primary objective was to quantify the spatial variation of trace metals and strontium isotope ratios ( 87 Sr: 86 Sr) for future and paired use with otolith microchemistry to track fish movement. Using ICP-OES, we identified that some trace metals, particularly strontium and barium as well as 87 Sr: 86 Sr ratios, varied spatially when analysing all water samples and revealed three distinct regions centring around the estuary, interior and outer regions. These differences were driven by variation in the underlying surface geology between the Clarence–Moreton Basin and the New England Block. Tidal influence also affected trace metals and 87 Sr: 86 Sr ratios throughout the estuarine area. We suggest that the level of differentiation identified in the current study has the potential to discriminate broad-scale fish movements among regions/habitats using otolith analysis, with fine scale movements best elucidated using complementary techniques.

Cigarette smoking and prostate cancer aggressiveness among African and European American men - Edgar T. Ellis; Brian J. Fairman; Shelbie D. Stahr; Jeannette T. Bensen; James L. Mohler; Lixin Song; Eboneé N. Butler; L. Joseph Su; Ping-Ching Hsu (Cancer Causes & Control, 2024)
Purpose Smoking is a modifiable lifestyle factor that has not been established as a prostate cancer risk factor, nor emphasized in prostate cancer prevention. Studies have shown that African American (AA) smokers have a poorer cancer prognosis than European Americans (EAs), while having a lower prevalence of heavy smoking. We examined the relationship between cigarette smoking and prostate cancer aggressiveness and assessed racial differences in smoking habits on the probability of high-aggressive prostate cancer. Methods Using data from the North Carolina-Louisiana Prostate Cancer Project ( n = 1,279), prostate cancer aggressiveness was defined as high or low based on Gleason scores, serum prostate-specific antigen levels, and tumor stage. Cigarette smoking was categorized as current, former, or never smokers. Multivariable logistic regression was used to estimate adjusted odds ratios (OR) and 95% confidence intervals (CI). Results Self-reported current (OR = 1.99; 95% CI 1.30–3.06) smoking was associated with high-aggressive prostate cancer relative to never smokers. When stratified by self-reported race, the odds of having high-aggressive cancer increased among AA current (OR = 3.58; 95% CI 2.04–6.28) and former smokers (OR = 2.21; 95% CI 1.38–3.53) compared to AA never smokers, but the odds were diminished among the EA stratum ( P self-reported race x smoking status = 0.003). Conclusion Cigarette smoking is associated with prostate cancer aggressiveness, a relationship modulated by self-reported race. Future research is needed to investigate types of cigarettes smoked and metabolic differences that may be contributing to the racial disparities observed.

Contribution of invasive carp (Cyprinus carpio) to fish biomass in rivers of the Murray–Darling Basin, Australia - Hayden T. Schilling; Gavin L. Butler; Katherine J. M. Cheshire; Dean M. Gilligan; Jerom R. Stocks; Jason D. Thiem; David A. Crook (Biological Invasions, 2024)
Following the introduction of the ‘Boolarra’ strain to Australia in the mid 1960’s, Common carp ( Cyprinus carpio ) rapidly spread in waterways across the Murray–Darling Basin (MDB) in southern-eastern Australia. A previous study of the population expansion based upon data up to the early 2000s suggested the carp population may have reached, and was fluctuating around, the ecosystem carrying capacity. It has been widely stated in the scientific literature and media that carp comprise up to 90% of fish biomass in MDB rivers; however, this figure is largely based on sparse data collected in the 1990s and the accuracy of this estimate is uncertain. Here, we analyse three decades (1994–2023) of electrofishing data to estimate the median proportion of total fish biomass contributed by carp across > 1,400 sites in lowland rivers ( 90%) by carp has declined from ≈ 33% of sites in the mid-1990s to ≈ 20% of sites. The proportion of biomass comprised by carp varied depending on the scale of analysis. Across the NSW MDB, carp accounted for a median of 57% (95% CI: 42.5–70.4) of fish biomass at the site level. At the river catchment scale estimates ranged from ≈ 45–66%. In contrast, the median proportion of carp within key rivers ranged from ≈ 46–80%, suggesting that carp can dominate total fish biomass in some rivers for short time-periods. The proportion of biomass contributed by carp at the NSW MDB scale was remarkably stable across decades, suggesting that the carrying capacity of carp may have been reached. Our revised estimates of the contribution of carp to overall fish biomass can facilitate informed debate around the dominance of carp in MDB rivers and provide important information for carp management in the future.

Pleistocene shifts in Great Basin hydroclimate seasonality govern the formation of lithium-rich paleolake deposits - Tripti Bhattacharya; Peter R. Brennan; Daniel E. Ibarra; Catherine A. Gagnon; Kristina L. Butler; Alexa Terrazas; Shaw Miller; Lee Ann Munk; David F. Boutt; Ran Feng; Stephanie N. Bullinger; Lucy Weisbeck (Quaternary Science Reviews, 2024)

Maternal contact and positive human interactions during lactation impact on pig stress resilience post-weaning - Katelyn Tomas; Jemma Savaglia; Kate J. Plush; Darryl N. D’Souza; Kym L. Butler; Paul H. Hemsworth; Alan J. Tilbrook (Applied Animal Behaviour Science, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

The value of adding black carbon to community monitoring of particulate matter - Rebecca A. Sugrue; Chelsea V. Preble; James D.A. Butler; Alaia J. Redon-Gabel; Pietro Marconi; Karan D. Shetty; Lee Ann L. Hill; Audrey M. Amezcua-Smith; Boris R. Lukanov; Thomas W. Kirchstetter (Atmospheric Environment, 2024)

Tailoring the time delay of deployable structures using the Intermediate Axis Theorem - Christopher S. Bentley; Jared Butler; Ryan L. Harne (Engineering Structures, 2024)

Fatty acid production and associated gene pathways are altered by increased salinity and dimethyl sulfoxide treatments during cryopreservation of Symbiodinium pilosum (Symbiodiniaceae) - Joseph K. Kihika; John K. Pearman; Susanna A. Wood; Lesley L. Rhodes; Kirsty F. Smith; Matthew R. Miller; Juliette Butler; Ken G. Ryan (Cryobiology, 2024)

Relationship between endocrine disrupting chemicals (phthalate metabolites, triclosan and bisphenols) and vitamin D in female subjects: An exploratory pilot study - Edwina Brennan; Alexandra E. Butler; Manjula Nandakumar; Kristie Thompson; Thozhukat Sathyapalan; Stephen L. Atkin (Chemosphere, 2024)

Environmental Effects on the Seasonal Distribution of an Estuarine Species Neoarius graeffei in Northern New South Wales, Australia - Lauren J. Stoot; Gavin L. Butler; Yuri Niella; Gregory S. Doran; Jason D. Thiem; Matthew D. Taylor; Lee J. Baumgartner (Estuaries and Coasts, 2024)
Coastal river systems provide essential habitats for a diversity of fish species that transition marine, estuarine, and freshwater environments to complete their lifecycles. Movement among and within these environments is important to access resources that optimise growth, survival, and reproduction. Knowledge on the movements, including the drivers, underpins management strategies, although this information is often lacking for many species. We used acoustic telemetry to quantify the relative importance of a range of abiotic stimuli in relation to seasonal movement patterns in blue salmon catfish Neoarius graeffei throughout an unregulated coastal river catchment, the Clarence River in northern New South Wales, Australia. Neoarius graeffei continuously occupied the Clarence River system for the duration of the 1-year study and were mostly confined to estuarine reaches, with occasional movement into freshwater habitats. Seasonal differences in habitat occupation were observed, with N. graeffei using habitats close to the river mouth in winter and upstream estuary habitats in spring. Broad-scale movement patterns were influenced by both water temperature and river flow, and high-flow events (> 1.5 m) resulted in short-term changes (~ 10 days) in habitat use. Sex-specific differences in seasonal habitat use were also observed which we hypothesise is linked to contrasting energetic investment in reproduction. The response of N. graeffei to changes in river flow highlights the need for assessment on these impacts for estuarine-dependent species more broadly, in the face of climate change and increased river regulation.

Accounting for herbaceous communities in process‐based models will advance our understanding of “grassy” ecosystems - Kevin R. Wilcox; Anping Chen; Meghan L. Avolio; Ethan E. Butler; Scott Collins; Rosie Fisher; Trevor Keenan; Nancy Y. Kiang; Alan K. Knapp; Sally E. Koerner; Lara Kueppers; Guopeng Liang; et al. (Global Change Biology, 2023)
Grassland and other herbaceous communities cover significant portions of Earth's terrestrial surface and provide many critical services, such as carbon sequestration, wildlife habitat, and food production. Forecasts of global change impacts on these services will require predictive tools, such as process‐based dynamic vegetation models. Yet, model representation of herbaceous communities and ecosystems lags substantially behind that of tree communities and forests. The limited representation of herbaceous communities within models arises from two important knowledge gaps: first, our empirical understanding of the principles governing herbaceous vegetation dynamics is either incomplete or does not provide mechanistic information necessary to drive herbaceous community processes with models; second, current model structure and parameterization of grass and other herbaceous plant functional types limits the ability of models to predict outcomes of competition and growth for herbaceous vegetation. In this review, we provide direction for addressing these gaps by: (1) presenting a brief history of how vegetation dynamics have been developed and incorporated into earth system models, (2) reporting on a model simulation activity to evaluate current model capability to represent herbaceous vegetation dynamics and ecosystem function, and (3) detailing several ecological properties and phenomena that should be a focus for both empiricists and modelers to improve representation of herbaceous vegetation in models. Together, empiricists and modelers can improve representation of herbaceous ecosystem processes within models. In so doing, we will greatly enhance our ability to forecast future states of the earth system, which is of high importance given the rapid rate of environmental change on our planet.

Impact of dairy farms on groundwater quality in a productive basin in the northeast of the Pampean Plain, Argentina - F. Cellone; L. Santucci; G. Borzi; C. Tanjal; C. Di Lello; L. Butler; J. Córdoba; L. Lamarche; J. Galliari; E. Melendi; M.I. Delgado; E. Carol (Groundwater for Sustainable Development, 2023)

Air pollution and the sequelae of COVID-19 patients: A multistate analysis - Michael Jerrett; Claudia L. Nau; Deborah R. Young; Rebecca K. Butler; Christina M. Batteate; Ariadna Padilla; Sara Y. Tartof; Jason Su; Richard T. Burnett; Michael J. Kleeman (Environmental Research, 2023)

Association of flame retardants, polybrominated diethyl ethers (PBDEs), with vitamin D in female subjects - Alexandra E. Butler; Edwina Brennan; Daniel S. Drage; Thozhukat Sathyapalan; Stephen L. Atkin (Chemosphere, 2023)

Feasibility and Tolerability of Daily Microgreen Consumption in Healthy Middle-Aged/Older Adults: A Randomized Crossover Trial - S. Holmes; K. Michell; M. Butler; B. Smith; A. Vazquez; E. Woolf; L. Grabos; S. Lee; S. Newman; M. Uchanski; T. Weir; S. Johnson (Journal of the Academy of Nutrition and Dietetics, 2023)

Scale dependency in fish beta diversity–hydrology linkages in lowland rivers - Robert J. Rolls; Ben Wolfenden; Jani Heino; Gavin L. Butler; Jason D. Thiem (Journal of Biogeography, 2023)
Aim A key aspect of biodiversity research is to determine the environmental drivers affecting the degree to which ecological assemblages vary in space (beta diversity). The strength and significance of environmental drivers of beta diversity is, however, influenced by the spatial extent over which beta diversity is assessed. Beta diversity of riverine biota is affected by flow variability. We examined hydrology–beta diversity relationships at two spatial extents (reaches vs. entire systems) within rivers to determine if relationships with hydrological variables are scale dependent or generalisable across spatial scales. Location Murray–Darling Basin, Australia. Taxon Freshwater fish. Methods Fish assemblage data were sourced from two monitoring programmes that sampled sites annually during 2014–2019 and spanned either reaches ( 1000 km) of five tributaries. Beta diversity was examined by calculating pairwise (incidence and abundance) dissimilarities for each year to compare temporal trends in beta diversity. Multi‐site dissimilarities were modelled against hydrological variables using beta regression. Results Inter‐annual change in assemblage composition was detected only at the extent of river reaches but not at the extent of river systems. Temporal variation in within‐river beta diversity showed inconsistent patterns when compared between the two spatial extents. Within‐river beta diversity relationships with hydrological gradients were inconsistent among rivers. Overall, statistical models explained much more variation in within‐river beta diversity when assessed at the reach extent when compared to broader river system extents. Main Conclusions Our findings highlight that changes in within‐river beta diversity are likely to depend on the spatial extent of sampling. Furthermore, inconsistent beta diversity–hydrology relationships among rivers suggest that both empirical evidence and theoretical predictions adopted in ecohydrology may not be transferable among river systems.

Differences in Intentional Weight Loss Strategies According to Race/ethnicity Among US Women, NHANES 2007 – 2018 - A. Gutierrez; R. Goode; M. Slining; L. Butler (Journal of the Academy of Nutrition and Dietetics, 2023)

Association of polychlorinated biphenyls with vitamin D in female subjects - Alexandra E. Butler; Edwina Brennan; Daniel S. Drage; Thozhukat Sathyapalan; Stephen L. Atkin (Environmental Research, 2023)

The effect of shade on sheep grazing pasture during summer conditions - Matthew I. Knight; Nick P. Linden; Kym L. Butler; Maxine Rice; Eric N. Ponnampalam; Ralph Behrendt; Ellen C. Jongman (Journal of Veterinary Behavior, 2023)

Blood chemistry and biliverdin differ according to reproduction and tourism in a free-living lizard - Susannah S. French; Erin L. Lewis; Kwanho C. Ki; Zachary E. Cullen; Alison C. Webb; Charles R. Knapp; John B. Iverson; Michael W. Butler (Journal of Comparative Physiology B, 2023)

Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

Correction to: Determining puma habitat suitability in the Eastern USA - Veronica Yovovich; Nathaniel Robinson; Hugh Robinson; Michael J. Manfredo; Shelby Perry; Jeremy T. Bruskotter; John A. Vucetich; Luis Aníbal Solórzano; Lydia A. Roe; Alison Lesure; Jamie Robertson; Tom Butler; et al. (Biodiversity and Conservation, 2023)

Determining puma habitat suitability in the Eastern USA - Veronica Yovovich; Nathaniel Robinson; Hugh Robinson; Michael J. Manfredo; Shelby Perry; Jeremy T. Bruskotter; John A. Vucetich; Luis Aníbal Solórzano; Lydia A. Roe; Alison Lesure; Jamie Robertson; Tom Butler; et al. (Biodiversity and Conservation, 2023)
Pumas ( Puma concolor ) were eliminated from most of the eastern USA a century ago. In the past couple of decades, their recovery in the West has increased puma dispersal into the Midwest, with some individuals even traveling to the East Coast. We combined published expert opinion data and a habitat suitability index in an analysis that identified 17 areas in the Upper Midwest, Ozarks, Appalachia, and New England that could potentially host puma populations in the future. Thirteen of these were larger than 10,000 km 2 and so likely to ensure a puma population’s long-term genetic health. Further, we quantified patch size, human density, livestock density, percent public land, and a sociocultural index reflecting wildlife values for comparing patches, as well as present a summary of current legislation relevant to puma management in the East. Our work may be useful in identifying suitable areas to restore pumas based not only on the quality of their biophysical habitat, but also on social values conducive to puma-human coexistence.

Crystallisation pathways of a mixed La Nd carbonate – Ambient temperature synthesis of the mineral lanthanite - Dylan L. Price; Ian B. Butler; Bryne T. Ngwenya; Linda A. Kirstein; Frank McDermott; Tiina O'Neill (Chemical Geology, 2023)

Phylogeography and taxonomy of Coleonyx elegans Gray 1845 (Squamata: Eublepharidae) in Mesoamerica: The Isthmus of Tehuantepec as an environmental barrier - Brett O. Butler; Lydia L. Smith; Oscar Flores-Villela (Molecular Phylogenetics and Evolution, 2023)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Towards open-source LOD2 modelling using convolutional neural networks - H. Muftah; T. S. L. Rowan; A. P. Butler (Modeling Earth Systems and Environment, 2022)
The aim of this paper is to classify and segment roofs using vertical aerial imagery to generate three-dimensional (3D) models. Such models can be used, for example, to evaluate the rainfall runoff from properties for rainwater harvesting and in assessing solar energy and roof insulation options. Aerial orthophotos and building footprints are used to extract individual roofs and bounding boxes, which are then fed into one neural network for classification and then another for segmentation. The approach initially implements transfer learning on a pre-trained VGG16 model. The first step achieves an accuracy of 95.39% as well as a F 1 score of 95%. The classified images are segmented using a fully convolutional network semantic segmentation model. The mask of the segmented roof planes is used to extract the coordinates of the roof edges and the nexus points using the Harris corner detector algorithm. The coordinates of the corners are then used to plot a 3D Level of Detail 2 (LOD2) representation of the building and the roof height is determined by calculating the maximum and minimum height of a Digital Surface Model LiDAR point cloud and known building height data. Subsequently the wireframe plot can be used to compute the roof area. This model achieved an accuracy of 80.2%, 96.1%, 96.0%, 85.1% and 91.1% for flat, hip, gable, cross-hip and mansard roofs, respectively.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Social group size influences pathogen transmission in salamanders - Kendra L. Ritchie; Vance T. Vredenburg; Shruti Chaukulkar; Helen M. Butler; Andrew G. Zink (Behavioral Ecology and Sociobiology, 2021)

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Diel and Seasonal Variability in Kelp Forest Soundscapes Off the Southern California Coast - Jack Butler; Camille M. L. S. Pagniello; Jules S. Jaffe; P. Ed Parnell; Ana Širović (Frontiers in Marine Science, 2021)
Soundscape ecology is a relatively new field that can provide insights into the structure and health of marine habitats. Though this field is growing, the acoustics of many marine habitats, including the giant kelp forests off Southern California, remain poorly studied. Here, we examine the diel and seasonal periodicity of kelp forest soundscapes within a protected and unprotected site off San Diego, CA. Singular value decomposition was used to identify frequency bands of interest, enabling tracking of these bands through seasons to examine their variability. Four frequency bands were identified: (1) 60–130 Hz, which encompassed a putative fish chorus, (2) 300–500 Hz, which encompassed a different putative fish chorus, (3) a band that encompassed humming generated by Plainfin Midshipmen Poricthys notatus (fundamental frequency: 85–95 Hz, and two subharmonics 175–185 Hz and 265–275 Hz), and (4) a band that encompassed the snaps of snapping shrimps from 2.5 to 7.5 kHz. Overall, kelp forest soundscapes exhibited diel and seasonal variability. In particular, the two putative fish choruses dominated the dusk soundscapes during late spring and summer, and the Midshipmen hums persisted throughout nights in summer. Snapping shrimp sounds exhibited stereotypic crepuscular activity, with peaks in acoustic energy in the 2.5–7.5 kHz band occurring at dusk and dawn. In addition, vessel noise was identified and found to exhibit strong seasonal and spatial variation. Vessel noise was greatest during August and September at the protected site and was generally lower during the winter and spring months. These findings help establish reference acoustic indices for the kelp forests off Southern California, within and outside of a protected area, and can provide resource managers with information on how well a marine reserve protects a species of interest, as well as the putative human visitation of these protected areas.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

One Size Does Not Fit All: Relationships between Size of Family Forest Holdings and Owner Attitudes and Behaviors - Brett J Butler; Jesse Caputo; Amanda L Robillard; Emma M Sass; Chris Sutherland (Journal of Forestry, 2021)
An estimated 10 million families, individuals, trusts, and estates own 39 percent of the forestland in the United States, excluding interior Alaska. Using segmented regression, the relationships between size of forest holdings and the attitudes and behaviors of these family forest ownerships were tested using data from the 2018 iteration of the USDA Forest Service’s National Woodland Owner Survey. All 16 variables tested have significant relationships with size of forest holdings, and 13 have one or more breakpoints, ranging from 40 to 5,854 ac, where the relationships between the variables change. Timber as a reason for owning, timber harvesting activities, management plan, advice received, land certified, tax program participation, cost share, recreation, land tenure, recreation, taxes and heirs as concerns, land transfer, and income from forestland have positive relationships with size of forest holdings; resident ownership has a negative relationship; and wildlife as a reason for owning and owner age have mixed relationships.

“They’re Constantly Cycling Through”: Lessons about Turnover and Collaborative Forest Planning - Kimberly J Coleman; William H Butler; Marc J Stern; Samantha L Beck (Journal of Forestry, 2021)
Within forest planning and management, collaboration has becoming increasingly widespread. Many collaborative projects take place over long time periods, and thus personnel turnover is inevitable within these groups. Scholars from the fields of business and organizational science have long studied strategies that organizations can use to prepare for and address turnover successfully. We draw from that literature and use it to examine the Collaborative Forest Landscape Restoration Program (CFLRP), a federal program aimed at bringing diverse stakeholders together to address the increasing costs, severity, and prevalence of wildfires in the United States. We conducted qualitative analysis of interviews, archival documents, and memos to explore what strategies are used within CFLRP groups to address turnover. We discuss our findings in light of the existing literature from business and organizational science and present insights about which strategies may be adaptable to collaborative natural resource management and which may require further research to assess their applicability to collaborative groups.

Seasonal, lunar, and diel patterns in spawning by the giant barrel sponge, Xestospongia muta - K. L. Neely; C. B. Butler (Coral Reefs, 2020)

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Correction to: Development of Decisional Values Statements for Lung Cancer Screening among African American Smokers - Randi M. Williams; Kenneth H. Beck; James Butler; Sunmin Lee; Min Qi Wang; Kathryn L. Taylor; Cheryl L. Knott (Journal of Cancer Education, 2020)

Development of Decisional Values Statements for Lung Cancer Screening Among African American Smokers - Randi M. Williams; Kenneth H. Beck; James Butler; Sunmin Lee; Min Qi Wang; Kathryn L. Taylor; Cheryl L. Knott (Journal of Cancer Education, 2020)

Robustness of trait connections across environmental gradients and growth forms - Habacuc Flores‐Moreno; Farideh Fazayeli; Arindam Banerjee; Abhirup Datta; Jens Kattge; Ethan E. Butler; Owen K. Atkin; Kirk Wythers; Ming Chen; Madhur Anand; Michael Bahn; Chaeho Byun; et al. (Global Ecology and Biogeography, 2019)
Aim Plant trait databases often contain traits that are correlated, but for whom direct (undirected statistical dependency) and indirect (mediated by other traits) connections may be confounded. The confounding of correlation and connection hinders our understanding of plant strategies, and how these vary among growth forms and climate zones. We identified the direct and indirect connections across plant traits relevant to competition, resource acquisition and reproductive strategies using a global database and explored whether connections within and between traits from different tissue types vary across climates and growth forms. Location Global. Major taxa studied Plants. Time period Present. Methods We used probabilistic graphical models and a database of 10 plant traits (leaf area, specific leaf area, mass‐ and area‐based leaf nitrogen and phosphorous content, leaf life span, plant height, stem specific density and seed mass) with 16,281 records to describe direct and indirect connections across woody and non‐woody plants across tropical, temperate, arid, cold and polar regions. Results Trait networks based on direct connections are sparser than those based on correlations. Land plants had high connectivity across traits within and between tissue types; leaf life span and stem specific density shared direct connections with all other traits. For both growth forms, two groups of traits form modules of more highly connected traits; one related to resource acquisition, the other to plant architecture and reproduction. Woody species had higher trait network modularity in polar compared to temperate and tropical climates, while non‐woody species did not show significant differences in modularity across climate regions. Main conclusions Plant traits are highly connected both within and across tissue types, yet traits segregate into persistent modules of traits. Variation in the modularity of trait networks suggests that trait connectivity is shaped by prevailing environmental conditions and demonstrates that plants of different growth forms use alternative strategies to cope with local conditions.

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Expression and localization of transient receptor potential channels in the bovine uterus epithelium throughout the estrous cycle - Maryam Ghavideldarestani; Alexandra E. Butler; Sadegh Shirian; Stephen L. Atkin (Molecular Biology Reports, 2019)

Quantitation of Purines from Pigeon Guano and Implications for Cryptococcus neoformans Survival During Infection - Jessica L. Chitty; David J. Edwards; Avril A. B. Robertson; Mark S. Butler; John A. Duley; Matthew A. Cooper; James A. Fraser (Mycopathologia, 2019)

Sex differences in vaccine-induced humoral immunity - Stephanie Fischinger; Carolyn M. Boudreau; Audrey L. Butler; Hendrik Streeck; Galit Alter (Seminars in Immunopathology, 2019)

Advances in Mechanistic Approaches to Quantifying Biophysical Fire Effects - J. J. O’Brien; J. K. Hiers; J. M. Varner; C. M. Hoffman; M. B. Dickinson; S. T. Michaletz; E. L. Loudermilk; B. W. Butler (Current Forestry Reports, 2018)

Correction to: Amphi‑enterobactin commonly produced among Vibrio campbellii and Vibrio harveyi strains can be taken up by a novel outer membrane protein FapA that also can transport canonical Fe(III)‑enterobactin - Hiroaki Naka; Zachary L. Reitz; Aneta M. Jelowicki; Alison Butler; Margo G. Haygood (JBIC Journal of Biological Inorganic Chemistry, 2018)

Amphi-enterobactin commonly produced among Vibrio campbellii and Vibrio harveyi strains can be taken up by a novel outer membrane protein FapA that also can transport canonical Fe(III)-enterobactin - Hiroaki Naka; Zachary L. Reitz; Aneta L. Jelowicki; Alison Butler; Margo G. Haygood (JBIC Journal of Biological Inorganic Chemistry, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Global biodiversity research tied up by juridical interpretations of access and benefit sharing - D. Neumann; A. V. Borisenko; J. A. Coddington; C. L. Häuser; C. R. Butler; A. Casino; J. C. Vogel; G. Haszprunar; P. Giere (Organisms Diversity & Evolution, 2018)

Combining otolith chemistry and telemetry to assess diadromous migration in pinkeye mullet, Trachystoma petardi (Actinopterygii, Mugiliformes) - Nathan G. Miles; Gavin L. Butler; Sandra L. Diamond; David P. Bishop; Dylan E. van der Meulen; Ivars Reinfelds; Chris T. Walsh (Hydrobiologia, 2018)

A Novel Aza-MBP Altered Peptide Ligand for the Treatment of Experimental Autoimmune Encephalomyelitis - Nicole N. M. Trager; Jonathan T. Butler; Jennifer Harmon; Joshua Mount; Maria Podbielska; Azizul Haque; Naren L. Banik; Craig C. Beeson (Molecular Neurobiology, 2018)

Methods for Increasing Cooperation Rates for Surveys of Family Forest Owners - Brett J. Butler; Jaketon H. Hewes; Mary L. Tyrrell; Sarah M. Butler (Small-scale Forestry, 2017)

Wheat cultivar susceptibility to Gaeumannomyces graminis var. tritici and influence on Pseudomonas fluorescence numbers in the rhizosphere - R. F. van Toor; S. Chng; R. M. Warren; R. C. Butler; M. G. Cromey; R. A. Craigie; B. L. McCloy (Australasian Plant Pathology, 2016)

Development and testing of a micro wind tunnel for on-site wind erosion simulations - Craig L. Strong; John F. Leys; Mike R. Raupach; Joanna E. Bullard; Hélène A. Aubault; Harry J. Butler; Grant H. McTainsh (Environmental Fluid Mechanics, 2016)

Silencing porcine genes significantly reduces human-anti-pig cytotoxicity profiles: an alternative to direct complement regulation - James R. Butler; Gregory R. Martens; Jose L. Estrada; Luz M. Reyes; Joseph M. Ladowski; Cesare Galli; Andrea Perota; Conor M. Cunningham; Matthew Tector; A. Joseph Tector (Transgenic Research, 2016)

The Application of Long-Lived Bivalve Sclerochronology in Environmental Baseline Monitoring - Juliane Steinhardt; Paul G. Butler; Michael L. Carroll; John Hartley (Frontiers in Marine Science, 2016)

Short-interval cortical inhibition and intracortical facilitation during submaximal voluntary contractions changes with fatigue - Sandra K. Hunter; Chris J. McNeil; Jane E. Butler; Simon C. Gandevia; Janet L. Taylor (Experimental Brain Research, 2016)

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Take-all decline in New Zealand wheat soils and the microorganisms associated with the potential mechanisms of disease suppression - Soonie Chng; Matthew G. Cromey; Sarah L. Dodd; Alison Stewart; Ruth C. Butler; Marlene V. Jaspers (Plant and Soil, 2015)

2nd International Conference on Progressive Multifocal Leukoencephalopathy (PML) 2015: JCV virology, progressive multifocal leukoencephalopathy pathogenesis, diagnosis and risk stratification, and new approaches to prevention and treatment - Andriani C. Patera; Scott L. Butler; Paola Cinque; David B. Clifford; Robert Elston; Robert L. Garcea; Eugene O. Major; Dejan Pavlovic; Ilse S. Peterson; Anne M. Ryan; Kenneth L. Tyler; Thomas Weber (Journal of NeuroVirology, 2015)

Eurasian snow cover variability and links to winter climate in the CMIP5 models - Jason C. Furtado; Judah L. Cohen; Amy H. Butler; Emily E. Riddle; Arun Kumar (Climate Dynamics, 2015)

Quantitative PCR to detect Gaeumannomyces graminis var. tritici in symptomatic and non-symptomatic wheat roots - S. Keenan; M. G. Cromey; S. A. Harrow; S. L. Bithell; R. C. Butler; S. S. Beard; A. R. Pitman (Australasian Plant Pathology, 2015)

Life cycle assessment of adsorbents for fluoride removal from drinking water in East Africa - Teshome L. Yami; Junyi Du; Laura R. Brunson; Jim F. Chamberlain; David A. Sabatini; Elizabeth C. Butler (The International Journal of Life Cycle Assessment, 2015)

Integrating Top-Down and Bottom-Up Adaptation Planning to Build Adaptive Capacity: A Structured Learning Approach - J. R. A. Butler; R. M. Wise; T. D. Skewes; E. L. Bohensky; N. Peterson; W. Suadnya; Y. Yanuartati; T. Handayani; P. Habibi; K. Puspadi; N. Bou; D. Vaghelo; et al. (Coastal Management, 2015)

Age and growth of mangrove red snapper Lutjanus argentimaculatus at its cool‐water‐range limits - T. P. Piddocke; G. L. Butler; P. A. Butcher; J. Stewart; D. J. Bucher; L. Christidis (Journal of Fish Biology, 2015)
This study investigates the age and growth of Lutjanus argentimaculatus at its southern (cooler) range limits in eastern Australia. Specimens were collected from New South Wales and southern Queensland between November 2011 and December 2013. Fork lengths ( L F ) ranged from 190 to 1019 mm, and ages ranged from 2+ to 57+ years. Growth was described by the von Bertalanffy growth function with coefficients L ∞ = 874·92 mm, K = 0·087 year −1 and t 0 = −2·76 years. Estimates of the instantaneous natural mortality rate ( M ) ranged from 0·072 to 0·25. The L F (mm) and mass ( W ; g) relationship was represented by the equation: . The maximum age of 57+ years is the oldest reported for any lutjanid and comparisons with tropical studies suggest that the age‐based demography of L. argentimaculatus follows a latitudinal gradient. High maximum ages and low natural mortality rates indicate considerable vulnerability to overexploitation at the species' cool‐water‐range limits. These results demonstrate the need to identify underlying processes driving latitudinal gradients in fish demography.

Scaffolds for Tendon and Ligament Repair and Regeneration - Anthony Ratcliffe; David L. Butler; Nathaniel A. Dyment; Paul J. Cagle; Christopher S. Proctor; Seena S. Ratcliffe; Evan L. Flatow (Annals of Biomedical Engineering, 2015)

Optimal visual–vestibular integration under conditions of conflicting intersensory motion profiles - John S. Butler; Jennifer L. Campos; Heinrich H. Bülthoff (Experimental Brain Research, 2015)

Displacement Forecasting Method in Brittle Crack Surrounding Rock Under Excavation Unloading Incorporating Opening Deformation - X. J. Li; W. M. Yang; L. G. Wang; I. B. Butler (Rock Mechanics and Rock Engineering, 2014)

Contributions of visual and proprioceptive information to travelled distance estimation during changing sensory congruencies - Jennifer L. Campos; John S. Butler; Heinrich H. Bülthoff (Experimental Brain Research, 2014)

Genetic diversity and population structure of sickleweed (Falcaria vulgaris; Apiaceae) in the upper Midwest USA - Sarbottam Piya; Madhav P. Nepal; Jack L. Butler; Gary E. Larson; Achal Neupane (Biological Invasions, 2014)

Light brown apple moth (Epiphyas postvittana) (Lepidoptera: Tortricidae) colonization of California - D. M. Suckling; L. D. Stringer; D. B. Baird; R. C. Butler; T. E. S. Sullivan; D. R. Lance; G. S. Simmons (Biological Invasions, 2014)

Application of stable isotope mixing models for defining trophic biomagnification pathways of mercury and selenium - H. J. Jones; K. M. Swadling; E. C. V. Butler; L. A. Barry; C. K. Macleod (Limnology and Oceanography, 2014)
Trophic models based on nitrogen stable isotope ratios ( δ 15 N) have been shown to predict changes in mercury (Hg) concentrations in fish; however, they are usually applied at the ecosystem scale and are rarely directed at known trophic pathways. We discuss a novel approach in which we combined gut contents analysis and stable isotope analyses ( δ 15 N and δ 13 C) into a Bayesian isotopic mixing model to provide a quantitative estimate of Hg and selenium (Se) biomagnification in an estuarine food web. Estimates of the relationship between total mercury (THg) and methylmercury (MeHg) were significantly improved in mixing model‐adjusted food webs over models that included all known prey sources. Spatial differences in dietary composition and MeHg bioavailability offer strong evidence that local food webs can have a significant effect on the biomagnification of Hg within benthic fish species. While no evidence of Se biomagnification was found, lower Se : Hg ratios at higher trophic levels could be attributed to increasing trophic Hg concentration. Furthermore, stable isotope analysis suggested Hg and Se biotransfer from benthic sources to fish. Overall, the findings highlight that isotope mixing models can be a significant aid in assessments of contaminant biomagnification, particularly when it is important to define food pathways to top predators.

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Larval Distribution and Behavior of Chrysomya rufifacies (Macquart) (Diptera: Calliphoridae) Relative to Other Species on Florida Black Bear (Carnivora: Ursidae) Decomposing Carcasses - S L Swiger; J A Hogsette; J F Butler (Neotropical Entomology, 2014)

Effect of β3 adrenoceptor activation in the basolateral amygdala on ethanol seeking behaviors - T. R. Butler; A. M. Chappell; J. L. Weiner (Psychopharmacology, 2014)

Yeast copper–zinc superoxide dismutase can be activated in the absence of its copper chaperone - Kevin W. Sea; Yuewei Sheng; Herman L. Lelie; Lindsay Kane Barnese; Armando Durazo; Joan Selverstone Valentine; Edith Butler Gralla (JBIC Journal of Biological Inorganic Chemistry, 2013)

Soil organic carbon dust emission: an omitted global source of atmospheric CO 2 - Adrian Chappell; Nicholas P. Webb; Harry J. Butler; Craig L. Strong; Grant H. McTainsh; John F. Leys; Raphael A. Viscarra Rossel (Global Change Biology, 2013)
Soil erosion redistributes soil organic carbon ( SOC ) within terrestrial ecosystems, to the atmosphere and oceans. Dust export is an essential component of the carbon (C) and carbon dioxide ( CO 2 ) budget because wind erosion contributes to the C cycle by removing selectively SOC from vast areas and transporting C dust quickly offshore; augmenting the net loss of C from terrestrial systems. However, the contribution of wind erosion to rates of C release and sequestration is poorly understood. Here, we describe how SOC dust emission is omitted from national C accounting, is an underestimated source of CO 2 and may accelerate SOC decomposition. Similarly, long dust residence times in the unshielded atmospheric environment may considerably increase CO 2 emission. We developed a first approximation to SOC enrichment for a well‐established dust emission model and quantified SOC dust emission for Australia (5.83 Tg CO 2 ‐e yr −1 ) and Australian agricultural soils (0.4 Tg CO 2 ‐e yr −1 ). These amount to underestimates for CO 2 emissions of ≈10% from combined C pools in Australia (year = 2000), ≈5% from Australian Rangelands and ≈3% of Australian Agricultural Soils by Kyoto Accounting. Northern hemisphere countries with greater dust emission than Australia are also likely to have much larger SOC dust emission. Therefore, omission of SOC dust emission likely represents a considerable underestimate from those nations’ C accounts. We suggest that the omission of SOC dust emission from C cycling and C accounting is a significant global source of uncertainty. Tracing the fate of wind‐eroded SOC in the dust cycle is therefore essential to quantify the release of CO 2 from SOC dust to the atmosphere and the contribution of SOC deposition to downwind C sinks.

CFSv2 ensemble prediction of the wintertime Arctic Oscillation - Emily E. Riddle; Amy H. Butler; Jason C. Furtado; Judah L. Cohen; Arun Kumar (Climate Dynamics, 2013)

Skeletal muscle adaptations to physical inactivity and subsequent retraining in young men - E. L. Campbell; O. R. Seynnes; R. Bottinelli; J. S. McPhee; P. J. Atherton; D. A. Jones; G. Butler-Browne; M. V. Narici (Biogerontology, 2013)

Influences of crop sequence, rainfall and irrigation, on relationships between Gaeumannomyces graminis var. tritici and take-all in New Zealand wheat fields - Sean L. Bithell; Ruth C. C. Butler; Alan C. McKay; Matthew G. Cromey (Australasian Plant Pathology, 2013)

Effects of different rates of Gaeumannomyces graminis var. tritici inoculum for detecting take-all suppression in soils - S. F. Chng; A. Stewart; M. G. Cromey; S. L. Dodd; R. C. Butler; M. V. Jaspers (Australasian Plant Pathology, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

Estimation of spawning habitats of market squid ( Doryteuthis opalescens ) from field surveys of eggs off Central and Southern California - Louis D. Zeidberg; John L. Butler; Darlene Ramon; Anthony Cossio; Kevin L. Stierhoff; Annette Henry (Marine Ecology, 2012)
Like many other loliginid squid, Doryteuthis (Loligo) opalescens deposits egg cases on the ocean floor. Depending upon temperature, egg cases may persist for 5–12 weeks before the paralarvae hatch. Because of this relatively long duration and squid’s pelagic life history, egg cases provide a practical life stage to survey. During 2001–2002, squid egg beds in Monterey Bay, Carmel Bay, and around the California Channel Islands were surveyed using a remotely operated vehicle with the goal of delineating the habitat of egg beds that are spawned during active commercial fishing. Egg cases were highly aggregated and densities reached 1338 capsules m −2 . Squid eggs were significantly shallower in Central California. Egg cases occurred between 20 and 93 m around the Channel Islands, and in Central California they were between 13 and 61 m. The temperatures in both regions were similar (10–12 °C), with some eggs in Southern California found up to 14.4 °C. Ninety‐five percent of eggs were found on sand, suggesting that temperature and substrate are stronger behavioral cues than depth to stimulate spawning. Suitable spawning habitat was defined by three criteria: sandy benthic substrate, temperatures between 10 and 14.4 °C, and depths between 20 and 70 m when the first two criteria hold. Additionally, within this defined area, oxygen concentration is quantified. The greatest commercial landings of market squid occur in both Central and Southern California during a time of year when water temperatures of 10–12 °C are prevalent in the 20–70 m depth range.

(2-Methoxyethoxy)acetic acid: a urinary biomarker of exposure for jet fuel JP-8 - Clayton B’Hymer; Patricia Mathias; Edward Krieg; Kenneth L. Cheever; Christine A. Toennis; John C. Clark; James S. Kesner; Roger L. Gibson; Mary Ann Butler (International Archives of Occupational and Environmental Health, 2012)

Multisensory integration in the estimation of walked distances - Jennifer L. Campos; John S. Butler; Heinrich H. Bülthoff (Experimental Brain Research, 2012)

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Nest box design for the study of diurnal raptors and owls is still an overlooked point in ecological, evolutionary and conservation studies: a review - Marcel M. Lambrechts; Karen L. Wiebe; Peter Sunde; Tapio Solonen; Fabrizio Sergio; Alexandre Roulin; Anders Pape Møller; Bernat C. López; Juan A. Fargallo; Klaus-Michael Exo; Giacomo Dell’Omo; David Costantini; et al. (Journal of Ornithology, 2012)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay - Rachel D. Burnside; Romela Pasion; Fady M. Mikhail; Andrew J. Carroll; Nathaniel H. Robin; Erin L. Youngs; Inder K. Gadi; Elizabeth Keitges; Vikram L. Jaswaney; Peter R. Papenhausen; Venkateswara R. Potluri; Hiba Risheg; et al. (Human Genetics, 2011)

Changes in Tundra Pond Limnology: Re-sampling Alaskan Ponds After 40 Years - Vanessa L. Lougheed; Malcolm G. Butler; Daniel C. McEwen; John E. Hobbie (Ambio, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Hyperglycemic oxoaldehyde, glyoxal, causes barrier dysfunction, cytoskeletal alterations, and inhibition of angiogenesis in vascular endothelial cells: aminoguanidine protection - Sean M. Sliman; Timothy D. Eubank; Sainath R. Kotha; M. Lakshmi Kuppusamy; Shariq I. Sherwani; Elizabeth Susan O’Connor Butler; Periannan Kuppusamy; Sashwati Roy; Clay B. Marsh; David M. Stern; Narasimham L. Parinandi (Molecular and Cellular Biochemistry, 2010)

Thinking and managing outside the box: coalescing connectivity networks to build region-wide resilience in coral reef ecosystems - R. S. Steneck; C. B. Paris; S. N. Arnold; M. C. Ablan-Lagman; A. C. Alcala; M. J. Butler; L. J. McCook; G. R. Russ; P. F. Sale (Coral Reefs, 2009)

Activation amplitude patterns do not change for back muscles but are altered for abdominal muscles between dominant and non-dominant hands during one-handed lifts - Heather L. Butler; Cheryl L. Hubley-Kozey; John W. Kozey (European Journal of Applied Physiology, 2009)

Tracking macaroni penguins during long foraging trips using ‘behavioural geolocation’ - Jonathan A. Green; Rory P. Wilson; Ian L. Boyd; Anthony J. Woakes; Chris J. Green; Patrick J. Butler (Polar Biology, 2009)

Use of weighted reference panels based on empirical estimates of ancestry for capturing untyped variation - Matthew R. L. Egyud; Zofia K. Z. Gajdos; Johannah L. Butler; Sam Tischfield; Loic Le Marchand; Laurence N. Kolonel; Christopher A. Haiman; Brian E. Henderson; Joel N. Hirschhorn (Human Genetics, 2009)

Redox-active antioxidant modulation of lipid signaling in vascular endothelial cells: vitamin C induces activation of phospholipase D through phospholipase A2, lipoxygenase, and cyclooxygenase - Emily Steinhour; Shariq I. Sherwani; Jessica N. Mazerik; Valorie Ciapala; Elizabeth O’Connor Butler; Jason P. Cruff; Ulysses Magalang; Sampath Parthasarathy; Chandan K. Sen; Clay B. Marsh; Periannan Kuppusamy; Narasimham L. Parinandi (Molecular and Cellular Biochemistry, 2008)

Ancient DNA reveals genotypic relationships among Oregon populations of the sea otter (Enhydra lutris) - Kim Valentine; Deborah A. Duffield; Lorelei E. Patrick; David R. Hatch; Virginia L. Butler; Roberta L. Hall; Niles Lehman (Conservation Genetics, 2008)

Reproductive biology of the endangered Oxleyan pygmy perch Nannoperca oxleyana Whitley - J. T. Knight; G. L. Butler; P. S. Smith; R. N. E. Wager (Journal of Fish Biology, 2007)
The reproductive biology of the Oxleyan pygmy perch Nannoperca oxleyana is described from simultaneous studies of wild populations in north‐eastern New South Wales and mature fish held in aquaria. In the wild, 50% of males and females matured at total lengths of 24·0–25·9 and 28·0–29·9 mm, respectively. The species displays sexual dichromatism during the spawning season, with males developing more intense red and brown fin and body colouration, and black pelvic fins. Captive male broodfish displayed territoriality during the breeding season, closely guarding sites within artificial, plant‐like substrata in which pairs of fish spawned adhesive eggs. Protracted serial spawning of wild and captive fish occurred from September to April and May at mean water temperatures ≥16·6° C and day length ≥10·7 h. Captive broodfish spawned on an average of 57% of days during the 256 day spawning period. Gonado‐somatic indices averaged 0·7% for all ripe males and 4·1–4·2% for all ripe females collected. Mean total and batch fecundities of captive females were 1323 eggs per fish and 7·8 eggs per fish per day, respectively, and relative fecundity was 587 eggs g −1 of body mass. Batch fecundity of wild females was estimated at 7·8 eggs per fish. The adaptive significance of this reproductive strategy in a harsh, variable environment is discussed.

Estimating density of intertidal ghost shrimps using counts of burrow openings. Is the method reliable? - Sarah Butler; Fiona L. Bird (Hydrobiologia, 2007)

Common genetic variation in eight genes of the GH/IGF1 axis does not contribute to adult height variation - Guillaume Lettre; Johannah L. Butler; Kristin G. Ardlie; Joel N. Hirschhorn (Human Genetics, 2007)

Visual cortex activation in kinesthetic guidance of reaching - W. G. Darling; R. J. Seitz; S. Peltier; L. Tellmann; A. J. Butler (Experimental Brain Research, 2007)

Life Cycle Impact Assessment of Greywater Recycling Technologies for New Developments - F. A. Memon; Z. Zheng; D. Butler; C. Shirley-Smith; S. Lui; C. Makropoulos; L. Avery (Environmental Monitoring and Assessment, 2007)

Population dynamics, distribution, and growth rate of tilapia (Oreochromis mossambicus) in the Salton Sea, California, with notes on bairdiella (Bairdiella icistia) and orangemouth corvina (Cynoscion xanthulus) - Lucille L. Caskey; Ralf R. Riedel; Barry Costa-Pierce; John Butler; Stuart H. Hurlbert (Hydrobiologia, 2007)

The effectiveness of bycatch reduction devices on crab pots at reducing capture and mortality of diamondback terrapins (Malaclemys terrapin) in Florida - Joseph A. Butler; George L. Heinrich (Estuaries and Coasts, 2007)

The origin of activity in the biceps brachii muscle during voluntary contractions of the contralateral elbow flexor muscles - Inge Zijdewind; Jane E. Butler; Simon C. Gandevia; Janet L. Taylor (Experimental Brain Research, 2006)

Variability of motor potentials evoked by transcranial magnetic stimulation depends on muscle activation - Warren G. Darling; Steven L. Wolf; Andrew J. Butler (Experimental Brain Research, 2006)

Patterns of Morphological Variation in a Sample of Cacao (Theobroma Cacao L.) Germplasm from the International Cocoa Genebank, Trinidad - Frances L. Bekele; Isaac Bekele; David R. Butler; Gillian G. Bidaisee (Genetic Resources and Crop Evolution, 2006)

Accounting for body condition improves allometric estimates of resting metabolic rates in fasting king penguins, Aptenodytes patagonicus - A. Fahlman; L. G. Halsey; P. J. Butler; D.R. Jones; A. Schmidt; S. Durand; G. Froget; C. -A. Bost; A. J. Woakes; C. Duchamp; Y. Handrich (Polar Biology, 2006)

Cooperation during prey digestion between workers and larvae in the ant, Pheidole spadonia - D. L. Cassill; J. Butler; S. B. Vinson; D. E. Wheeler (Insectes Sociaux, 2005)

Effects of dietary supplementation with vitamins C and E on muscle function during and after eccentric contractions in humans - A. Shafat; P. Butler; R. L. Jensen; A. E. Donnelly (European Journal of Applied Physiology, 2004)

Viable Transgenic Goats Derived from Skin Cells - Esmail Behboodi; Erdogan Memili; David T. Melican; Margaret M. Destrempes; Susan A. Overton; Jennifer L. Williams; Peter A. Flanagan; Robin E. Butler; Hetty Liem; Li How Chen; Harry M. Meade; William G. Gavin; et al. (Transgenic Research, 2004)

In Search of a Conceptualization of Multiple Sclerosis: A Historical Perspective - Michelle A. Butler; Thomas L. Bennett (Neuropsychology Review, 2003)

Photochemical reactivity of siderophores produced by marine heterotrophic bacteria and cyanobacteria based on characteristic Fe(III) binding groups - Katherine Barbeau; Eden L. Rue; Charles G. Trick; Kenneth W. Bruland; Alison Butler (Limnology and Oceanography, 2003)
Siderophores, high‐affinity Fe(III) ligands produced by microorganisms to facilitate iron acquisition, might contribute significantly to dissolved Fe(III) complexation in ocean surface waters. In previous work, we demonstrated the photoreactivity of the ferric ion complexes of several α‐hydroxy carboxylic acid—containing siderophores produced by heterotrophic marine bacteria. Here, we expand on our earlier studies and detail the photoreactivity of additional siderophores produced by both heterotrophic marine bacteria and marine cyanobacteria, making comparisons to synthetic and terrestrial siderophores that lack the α‐hydroxy carboxylate group. Our results suggest that, in addition to secondary photochemical reaction pathways involving reactive oxygen species, direct photolysis of Fe(III)‐siderophore complexes might be a significant source of Fe(II) and reactive Fe(III) in ocean surface waters. Our findings further indicate that the photoreactivity of siderophores is primarily determined by the chemical structure of the Fe(III) binding groups that they possess—hydroxamate, catecholate, or α‐hydroxy carboxylate moieties. Hydroxamate groups are photochemically resistant regardless of Fe(III) complexation. Catecholates, in contrast, are susceptible to photooxidation in the uncomplexed form but stabilized against photooxidation when ferrated. α‐Hydroxy carboxylate groups are stable as the uncomplexed acid, but when coordinated to Fe(III), these moieties undergo light‐induced ligand oxidation and reduction of Fe(III) to Fe(II). These photochemical properties appear to determine the reactivity and fate of Fe(III)‐binding siderophores in ocean surface waters, which in turn might significantly influence the biogeochemical cycling of iron.

Comparative In Vitro Surveillance of Amoxicillin-Clavulanic Acid and Four Oral Comparators Against 21,232 Clinical Isolates from Europe - D. J. Hoban; S. K. Bouchillon; J. L. Johnson; G. G. Zhanel; D. L. Butler; K. A. Saunders; L. A. Miller; J. A. Poupard (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Relationship Between Six Years of Corn Yields and Terrain Attributes - Thomas C. Kaspar; Thomas S. Colvin; Daniel B. Jaynes; Douglas L. Karlen; David E. James; David W. Meek; Daniel Pulido; Howard Butler (Precision Agriculture, 2003)

Reduced intracortical inhibition and facilitation of corticospinal neurons in musicians - Michael A. Nordstrom; Sophie L. Butler (Experimental Brain Research, 2002)

Comparative In Vitro Potency of Gemifloxacin and Fluoroquinolones Against Recent European Clinical Isolates from a Global Surveillance Study - D. Hoban; S. Bouchillon; J. Johnson; G. Zhanel; D. Butler; L. Miller; J. Poupard; the Gemifloxacin Surveillance Study Research Group (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Quality of life and psychosexual adjustment after prophylactic oophorectomy for a family history of ovarian cancer - L. Elit; M.J. Esplen; K. Butler; S. Narod (Familial Cancer, 2001)

Effects of rotenone on aquatic invertebrate communities in prairie wetlands - Christina L. Melaas; Kyle D. Zimmer; Malcolm G. Butler; Mark A. Hanson (Hydrobiologia, 2001)

Task-dependent control of human masseter muscles from ipsilateral and contralateral motor cortex - Sophie L. Butler; Timothy S. Miles; Philip D. Thompson; Michael A. Nordstrom (Experimental Brain Research, 2001)

Changes in muscle afferents, motoneurons and motor drive during muscle fatigue - Janet L. Taylor; Jane E. Butler; S. C. Gandevia (European Journal of Applied Physiology, 2000)

Caffeic Acid-Induced Changes in Plant–Water Relationships and Photosynthesis in Leafy Spurge Euphorbia esula - Richard R. Barkosky; Frank A. Einhellig; Jack L. Butler (Journal of Chemical Ecology, 2000)

Identification of genomic regions associated with stay green in sorghum by testing RILs in multiple environments - Y. Z. Tao; R. G. Henzell; D. R. Jordan; D. G. Butler; A. M. Kelly; C. L. McIntyre (Theoretical and Applied Genetics, 2000)

Mechanisms of Hydroquinone-Induced Growth Reduction in Leafy Spurge - Richard R. Barkosky; Jack L. Butler; Frank A. Einhellig (Journal of Chemical Ecology, 1999)

Opposite changes in myosin heavy chain composition of human masseter and biceps brachii muscles during aging - M. Monemi; P.-O. Eriksson; F. Kadi; G. S. Butler-Browne; L.-E. Thornell (Journal of Muscle Research and Cell Motility, 1999)

Cellular adaptation of the trapezius muscle in strength-trained athletes - Fawzi Kadi; Anders Eriksson; Staffan Holmner; Gillian S. Butler-Browne; L.-E. Thornell (Histochemistry and Cell Biology, 1999)

The β enolase subunit displays three different patterns of microheterogeneity in human striated muscle - T. Merkulova; L-E. Thornell; G. Butler-Browne; C. Oberlin; M. Lucas; N. Lamandé; M. Lazar; A. Keller (Journal of Muscle Research and Cell Motility, 1999)

Differential effects of a six-day immobilization on newborn rat soleus muscles at two developmental stages - F. Picquet; L. Stevens; G. S. Butler-Browne; Y. Mounier (Journal of Muscle Research and Cell Motility, 1998)

Corpuscles of Stannius and stanniocalcin-like immunoreactivity in the white sucker ( Catostomus commersoni ): evidence for a new cell-type - D. H. Zhang; G. Y. Oudit; L. E. Marra; D. G. Butler; J. H. Youson (Cell and Tissue Research, 1998)

Construction of an RFLP linkage map for cultivated sunflower - C. C. Jan; B. A. Vick; J. F. Miller; A. L. Kahler; E. T. Butler III. (Theoretical and Applied Genetics, 1998)

Effect of contraction strength on responses in biceps brachii and adductor pollicis to transcranial magnetic stimulation - J. L. Taylor; Gabrielle M. Allen; Jane E. Butler; S. C. Gandevia (Experimental Brain Research, 1997)

Interstitial fluid flow in tendons or ligaments: A porous medium finite element simulation - S. L. Butler; S. S. Kohles; R. J. Thielke; C. Chen; R. Vanderby (Medical & Biological Engineering & Computing, 1997)

Conservation Genetics of North American Freshwater Mussels Amblema and Megalonaias - Margaret Mulvey; Charles Lydeard; Debra L. Pyer; Kimberly M. Hicks; Jayne Brim‐Box; James D. Williams; Robert S. Butler (Conservation Biology, 1997)
Freshwater bivalves are among the most endangered groups of organisms in North America. Efforts to protect the declining mussel fauna are confounded by ambiguities associated with recognition of distinct evolutionary entities or species. This, in part, is due to the paucity of reliable morphological characters for differentiating taxa. We have employed allozymes and DNA sequence data to search for diagnosably distinct evolutionary entities within two problematic genera of unionid mussels, Amblema and Megalonaias. Within the genus Amblema three species are recognized based on our DNA sequence data for the mitochondrial 16S rRNA and allozyme data (Amblema neislerii, A. plicata, and A. elliotti). Only one taxonomically distinct entity is recognized within the genus Megalonaias—M. nervosa. Megalonaias boykiniana of the Apalachicolan Region is not diagnosable and does not warrant specific taxonomic status. Interestingly, Megalonaias from west of the Mississippi River, including the Mississippi, exhibited an allozyme and mtDNA haplotype frequency shift suggestive of an east‐west dichotomy. The results of this study eliminate one subspecies of Amblema and increase the range of A. plicata. This should not affect the conservation status of “currently stable” assigned to A. plicata by Williams et al. (1993). The conservation status of A. elliotti needs to be reexamined because its distribution appears to be limited to the Coosa River System in Alabama and Georgia.

Contractile properties and myosin heavy chain composition of newborn rat soleus muscles at different stages of postnatal development - F. PICQUET; L. STEVENS; G. S. BUTLER-BROWNE; Y. MOUNIER (Journal of Muscle Research and Cell Motility, 1997)

Condensed tannins in Leucaena and their relation to psyllid resistance - R. A. Wheeler; W. R. Chaney; L. G. Butler; J. L. Brewbaker (Agroforestry Systems, 1994)

Detection of DNA and E7 transcripts of human papillomavirus types 16, 18, 31 and 33, TGF? and GM-CSF transcripts in cervical cancers and precancers - L. Ho; G. Terry; B. Mansell; B. Butler; A. Singer (Archives of Virology, 1994)

Stress or heat shock protein synthesis and cellular filamentation in psychrophilic and psychrotrophic bacteria - Kirk L. McCallum; Barbara J. Butler; William E. Inniss (Archives of Microbiology, 1989)

Methyl parathion persistence in soil following simulated spillage - L. C. Butler; D. C. Staiff; J. E. Davis (Archives of Environmental Contamination and Toxicology, 1981)

The kinetics of methylmercury administered repeatedly to rats - L. Magos; W. H. Butler (Archives of Toxicology, 1976)

Study of the phenolic compounds in potato tubers during storage - C. C. Craft; H. W. Siegelman; W. L. Butler (American Journal of Potato Research, 1958)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)

Sectional notes - H. W. Poulsen; H. G. Zuckerman; C. H. Metzger; W. B. Ward; W. C. Edmundson; E. R. Bennet; R. A. Jehle; A. B. Beaumont; John S. Gardner; E. L. Newdick; Frank W. Hussey; E. J. Wheeler; et al. (American Journal of Potato Research, 1934)

Preliminary seed certification notes - E. R. Dykeman; C. H. Hadley; W. A. McCubbin; Harold L. Bailey; O Butler; M. F. Barrus; R. F. Payne; N. W. Glimes; H. O. Werner; W. Stuart; Donald Folsom; W. H. M. (American Journal of Potato Research, 1923)